2021
DOI: 10.1007/s12031-020-01767-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Coronavirus (CoV) Pathogenesis and Emerging Pathogen SARS-CoV-2 in the Nervous System: A Review on Neurological Impairments and Manifestations

Abstract: The coronavirus disease 2019 pandemic is an issue of global significance that has taken the lives of many across the world. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the virus responsible for its pathogenesis. The pulmonary manifestations of COVID-19 have been well described in the literature. Initially, it was thought to be limited to the respiratory system; however, we now recognize that COVID-19 also affects several other organs, including the nervous system. Two similar human coronav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
111
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 146 publications
0
111
0
10
Order By: Relevance
“…Our patients presented severe swallowing disorders, facial akinesia, absence of oculomotricity and lack of motor interaction to stimulation, without any structural brain MRI signs of inflammatory, vascular, degenerative, or infectious encephalopathy. The pathogenic mechanism explaining COVID-related neurological disorders and encephalopathy in particular, is the topic of intense discussion (2,(20)(21)(22)(23). Indeed, it remains undetermined whether SARS-CoV-2 causes direct brain damages (possibly by affecting the olfactory nerves and migrating retrogradely) or whether the cause is indirect, due to an excessive inflammatory response (cytokine storm) or the trigger of an autoimmune response by the virus (24), but more evidence suggest a migration to the central nervous system via transfer across the blood-brain barrier (20,23).…”
Section: Discussionmentioning
confidence: 99%
“…Our patients presented severe swallowing disorders, facial akinesia, absence of oculomotricity and lack of motor interaction to stimulation, without any structural brain MRI signs of inflammatory, vascular, degenerative, or infectious encephalopathy. The pathogenic mechanism explaining COVID-related neurological disorders and encephalopathy in particular, is the topic of intense discussion (2,(20)(21)(22)(23). Indeed, it remains undetermined whether SARS-CoV-2 causes direct brain damages (possibly by affecting the olfactory nerves and migrating retrogradely) or whether the cause is indirect, due to an excessive inflammatory response (cytokine storm) or the trigger of an autoimmune response by the virus (24), but more evidence suggest a migration to the central nervous system via transfer across the blood-brain barrier (20,23).…”
Section: Discussionmentioning
confidence: 99%
“…Large studies have reported the development of autoantibodies after COVID-19, which were also shown to be associated with disease severity [ 32 34 ]. The observed neurological impairment in COVID-19 [ 35 ] has been linked to both a direct effect of SARS-CoV‑2 on neurons and to autoimmune mechanisms [ 36 ]. A higher number of peripheral neuropathies (Guillain–Barré syndrome) and polyneuropathies with associated muscle denervation are observed in SARS-CoV-2 patients [ 37 ], which could be part of Long-COVID [ 34 , 38 ].…”
Section: The Covid-19 Vaccination In Everyday Clinical Practicementioning
confidence: 99%
“…The extent to which pre-existing chronic liver conditions affect COVID-19 related complications remains to be elucidated. Smell and taste sensations as well as increased incidence of ischemic stroke have been observed in individuals with COVID-19 [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%